Neural correlates of early cognitive dysfunction in Parkinson's disease. Issue 5 (28th March 2019) - Weil, Rimona S.; Winston, Joel S.; Leyland, Louise‐Ann; Pappa, Katerina; Mahmood, Ribeya B.; Morris, Huw R.; Rees, Geraint
Abstract: Objective: Dementia is a common and feared aspect of Parkinson's disease but there are no robust predictors of cognitive outcome. Visuoperceptual deficits are linked to risk of dementia in Parkinson's disease but whether they predict cognitive change is not known, and the neural substrates of visuoperceptual dysfunction in Parkinson's have not yet been identified. Methods: We compared patients with Parkinson's disease and unaffected controls who underwent BOLD fMRI while performing our previously validated visuoperceptual task and tested how functional connectivity between task‐specific regions and the rest of the brain differed between patients who performed well and poorly in the task. Results: We show that task performance at baseline predicts change in cognition in Parkinson's disease after 1 year. Our task‐based fMRI study showed that the performance in this task is associated with activity in the posterior cingulate cortex/precuneus. We found that functional connectivity between this region and dorsomedial prefrontal cortex was reduced in poor performers compared with good performers of this task. Interpretation: Our findings suggest that functional connectivity is reduced between posterior and anterior hubs of the default mode network in Parkinson's patients who are likely to progress to worsening cognitive dysfunction. Our work implicates posterior default mode nodes and their connections as key brain regions in early stages of dementia in Parkinson's disease.